Comparison of projection for selected European countries with focus on ageing and its effect on public expenditures for health and social care - Dizman, Hande Göksu (2023)
In the past century, fertility rates and mortality rates in the world have been decreasing. On the other hand, life expectancy has been going up. These results ageing in the populations. Ageing creates a challenge to public financing of health and social care. This paper compares the current demographic trends in Germany, France, Italy, and Spain, aims to project their populations until the age 2050, compare the findings and analyse ageing effect on public expenditures in these countries. In this paper, it has been concluded that scope countries face ageing in their population for a long time, moreover it has been found that the ageing would continue until 2050. Although the scoped countries have ageing in their populations, it has not been found clear effects on public expenditures in terms of health, pension, and education. Even though the financial effects are not crystal clear in the government expenditure side, it is observed of an increasing in the spendings for older generations. There should be taken various precautions to prevent ageing in the society and its financial effects. Therefore, in the last part of this thesis, pension reforms and migration are discussed as solution.